2020
DOI: 10.1371/journal.pone.0227145
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-concept for a non-invasive, portable, and wireless device for cardiovascular monitoring in pediatric patients

Abstract: Measurement of cardiac function is vital for the health of pediatric patients with heart disease. Standard tools to measure function including echocardiogram and magnetic residence imaging are time intensive, costly, and have limited accessibility. The Vivio is a novel, non-invasive, handheld device that screens for cardiac dysfunction by analyzing intrinsic frequencies (IF) ω 1 and ω 2 of carotid artery waveforms. Prior studies demonstrated that left ventricular ejection fraction can be derived from IFs in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In this study, we applied invasively measured aortic pressure waveforms to extract IF indices and quantify LV-arterial coupling through ∆ω. However, arterial pressure waveforms can be easily recorded non-invasively by applanation tonometry from the carotid artery (O'Rourke et al 2001, Nelson et al 2010), a smartphone (Pahlevan et al 2017) or smartphone-based handheld devices (Armenian et al 2018, Miller et al 2020. Thus, IF method has the potential to facilitate post-procedure follow-up in assessing cardiac and systemic circulation performance post TAVR procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we applied invasively measured aortic pressure waveforms to extract IF indices and quantify LV-arterial coupling through ∆ω. However, arterial pressure waveforms can be easily recorded non-invasively by applanation tonometry from the carotid artery (O'Rourke et al 2001, Nelson et al 2010), a smartphone (Pahlevan et al 2017) or smartphone-based handheld devices (Armenian et al 2018, Miller et al 2020. Thus, IF method has the potential to facilitate post-procedure follow-up in assessing cardiac and systemic circulation performance post TAVR procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous wave analysis techniques have been proposed to study the patterns found in these waves in order to uncover clinically valuable information, such as pulse wave analysis (Davies et al 2006) as well as separation into backwards and forwards components (Manisty et al 2010). Many of these methods have demonstrated efficacy in predicting or capturing relevant clinical metrics through analysis of both pressure and flow measurements (Mynard et al 2020), although pressure wave-only analysis methods (such as reservoirexcess pressure Parker 2020, Armstrong et al 2021), wave condition number (Pahlevan and Mazandarani 2020) and intrinsic frequency (Pahlevan et al 2014, Cooper et al 2021) have recently enjoyed increased traction due to the immense interest in obtaining blood pressure measurements cheaply, easily and non-invasively (Pahlevan et al 2017, Miller et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that there was a significant difference in w 1 among different age groups (Miller et al 2020); particularly, w 1 of the age group from 0 to 4 years old showed significant difference from the that of the adult cohort (Miller et al 2020). Therefore, we divided the study population into three age groups: 0-6 years old, 7-13 years old, and 14-20 years old.…”
Section: Parameter Selection and Analysismentioning
confidence: 97%